A Review of Pythagoras Theorem and Its Applications in the Construction Industry - Philemon, Mutabazi (Kabale University, 2022)
A Mathematics Project to be submitted to the Faculty of Science for the Award of a Degree of Bachelor of Science with Education of Kabale University